Efektivitas Campuran Indaziflam dan Glifosat untuk Pengendalian Gulma pada Areal Tanaman Kelapa Sawit Menghasilkan - Wiharti Oktaria Purba; Hari Priwiratama; Agus Susanto (Pusat Penelitian Kelapa Sawit, 2020)
Tank mixing of pre and post emergence herbicides with proper timing application is one potential way to reduce the rotation of herbicide application per year. An experiment was conducted in the field of 10 years old mature oil palm using the mixture of indaziflam 50 - 150 g a.i./ha and glyphosate 135 g a.i./ha. The standard herbicide used in the estate (mixture of methyl-metsulfuron 10 g a.i/ha and glyphosate 135 g a.i./ha) was used as a comparison. The experiment was designed by randomized block of 6 treatments and 4 repetitions. Herbicides were applied in rotation based on the designed timetable following field condition and certain policy in the estate. Indaziflam had shown its ability to suppress the growth of weed up to 9 months after application, just by the lowest dosage of 50 g b.a./ha. Indaziflam is safe to be used in the plantation as it showed no toxic nor negative effects to the oil palm. The mixture of indaziflam and standard herbicide have also reduced the rotation of herbicide application to twice a year.